Implementasi Pembiasaan Tahsin Al-Qur’an Bagi Siswa Kelas 1 Guna Melatih Kemampuan Membaca Al-Qur’an Sejak Dini Di Madrasah Ibtidaiyah - Mursid Mursid; Zakiyatun Nafisah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
This research is motivated by the phenomenon of children's lack of ability to read the Qur'an in this age of technological development. Based on these problems, we were moved to conduct research at MI Al-Khoiriyah 2 Semarang where this Madrasah featured a program namely Tahsin al-Qur'an. The purpose of this research is first, to find out how the application of tahsin program to improve the ability to read the Qur'an class 1 MI Al-Khoiriyah 2 Semarang. Second, to find out the supporting and inhibiting factors of the implementation of the tahsin al-Qur'an program at Madrasah Ibtidaiyah. Third, to find out how the influence of tahsin program to improve the ability to read al-Qur'an of grade 1 students in Madrasah Ibtidaiyah. This type of research is qualitative research with observation and interview methods. The data source of this research is the interview result from the companion teacher of tahsin program of grade 1 of Madrasah Ibtidaiyah Al-Khoiriyyah 2 Semarang. The results of this study indicate that the application of the tahsin program at MI Al-Khoiriyah 2 Semarang has a significant influence on improving children's ability to read the Qur'an from an early age. In the learning process the teacher uses the reading and listening method. The teacher also models the correct reading and justifies the wrong reading to the students.